Conceptual framework for acute community health care services – Illustrated by assessing the development of services in Denmark. (May 2023) - Fournaise, Anders; Andersen-Ranberg, Karen; Lauridsen, Jørgen T.; Espersen, Kurt; Gudex, Claire; Bech, Mickael
Abstract: Acute community health care services can support continuity of care by acting as a bridge between the primary and secondary health care sectors in the early detection of acute disease and provision of treatment and care. Although acute community health care services are a political priority in many countries, the literature on their organization and effect is limited. We present a conceptual framework for describing acute community health care services that can be used to support the policies and guidelines for such services. For illustrative purposes, we apply the framework to the Danish acute community health care services using implementation data from 2020 and identify gaps and opportunities for learning. The framework identifies two key pairs of dimensions: (1) capacity & capability, and (2) coordination & collaboration. These dimensions, together with the governance structure and quality assurance initiatives, are of key importance to the effect of acute community health care services. While all Danish municipalities have implemented acute community health care services, application of the framework indicates considerable variation in their approaches. The conceptual framework provides a systematic approach supporting the development, implementation, evaluation, and monitoring of acute community health care services and can assist policymakers at both national and local levels in this work. Highlights: A novel conceptual framework for describing acute community health care services. We discuss implications of organizational differences for performance and cross-sectoral collaboration. Illustrative example comparing acute community health care services in Danish municipalities.